A case-series of bloodstream infections caused by the Meyerozyma guilliermondii species complex at a reference center of oncology in Brazil. (4th June 2020) - Chaves, Alessandra Leal Silva; Trilles, Luciana; Alves, Gabriela Machado; Figueiredo-Carvalho, Maria Helena Galdino; Brito-Santos, Fábio; Coelho, Rowena Alves; Martins, Ianick S; Almeida-Paes, Rodrigo
Abstract: Bloodstream infections (BSI) caused by Candida species are the fourth cause of healthcare associated infections worldwide. Non- albicans Candida species emerged in the last decades as agents of serious diseases. In this study, clinical and microbiological aspects of six patients with BSI due to the Meyerozyma ( Candida ) guilliermondii species complex from an oncology reference center in Brazil, were evaluated. To describe demographic and clinical characteristics, medical records of the patients were reviewed. Molecular identification of the isolates was performed by ITS1-5.8S-ITS2 region sequencing. Antifungal susceptibility was evaluated by the EUCAST method and the minimal inhibitory concentrations (MIC) assessed according to the epidemiological cutoff values. Virulence associated phenotypes of the isolates were also studied. Ten isolates from the six patients were evaluated. Five of them were identified as Meyerozyma guilliermondii and the others as Meyerozyma caribbica . One patient was infected with two M. caribbica isolates with different genetic backgrounds. High MICs were observed for fluconazole and echinocandins. Non-wild type isolates to voriconazole appeared in one patient previously treated with this azole. Additionally, two patients survived, despite infected with non-wild type strains for fluconazole and treated with this drug. All isolates produced hemolysin, which was not associated with a poor prognosis, and none produced phospholipases. Aspartic proteases, phytase, and esterase were detected in a few isolates. This study shows the reduced antifungal susceptibility and a variable production of virulence-related enzymes by Meyerozyma spp. In addition, it highlights the poor prognosis of neutropenic patients with BSI caused by this emerging species complex. Lay Abstract: Our manuscript describes demographic, clinical and microbiological characteristics of patients with bloodstream infection by the Meyerozyma guilliermondii species complex at a reference center in oncology in Brazil.